Economic voting in Portuguese municipal elections - Martins, Rodrigo Caldeira de Almeida (2013)
This paper analyses the impact of economic conditions on Portuguese municipal electoral outcomes. We use two extensive datasets to estimate an economic voting model which accounts for the possibility that different levels of government have different levels of responsibility for economic outcomes and for clarity of government responsibility. The empirical results indicate that the performance of the national economy is important especially if local governments are of the same party as the central government. The municipal situation is also relevant particularly in scenarios of greater clarity of national and sub-national government responsibility.